Why Islamists Go Green. Politics, Religion and the Environment by Emmanuel Karagiannis - Hudriansyah, Hudriansyah (Islamic Studies Review, 2024)
Why Islamists Go Green. Politics, Religion and the Environment by Emmanuel Karagiannis. Edinburgh University Press, 2023. Islamist groups have been examined from various perspectives, with most studies focused on these groups’ use of violence, which provides a misleading perspective of how Muslim societies evolve and how they interact with the rest of the world. As a result, there is a lack of focus on Islamist movements’ relationship with the environment. Emmanuel Karagiannis’s Why Islamists Go Green is the first well-researched work that reveals important trends in how Islamism interacts with the environment (p. xi). The author focuses on five Islamist groups – the Muslim Brotherhood, Hizb ut-Tahrir, Hizbullah, Hamas, and Salafi-jihadist groups such as al-Qaeda and ISIS – and the religious and political foundations for the formation of their green policies based on Islamic texts, rulings and principles (p. 10). The author’s argument convincingly sheds light on the basic principles and essence of Islamist environmentalism as it includes extensive literature and interviews with representatives of these movements and an analysis of online resources and initiatives from the various parties and groups (pp. 11-13).